2006
DOI: 10.1890/0012-9658(2006)87[3014:raopat]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

RESOURCES AND OFFSPRING PROVISIONING: A TEST OF THE TREXLER-DeANGELIS MODEL FOR MATROTROPHY EVOLUTION

Abstract: Theoretical models of the evolution of matrotrophy from a lecithotrophic ancestor suggest that resource availability plays a major role in selective scenarios favoring a change in offspring provisioning. We examined effects of feeding level on embryo provisioning in the livebearing fish Gambusia geiseri, a species with dual provisioning of embryos via both yolk sequestered in large eggs and post-fertilization mother-to-embryo nutrient transfer. Females were fed either once per day or once every three days for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 23 publications
4
50
1
Order By: Relevance
“…In short, pregnant females were injected with 8 ll 3 H-leucine (84 Ci/mmole) in the caudal peduncle and 2 h after the injection the females were euthanized using an overdose of MS-222 (Tricaine Methanesulfonate). In the ensuing dissection a sample of the liver was taken to assess uptake of the labeled source by the mother, and individual embryos were carefully dissected from the ovary to remove all maternal tissues, rinsed twice in distilled water and dried for 10 days at 40°C, weighed to the nearest 0.1 mg, and prepared for liquid scintillation assay as described by Marsh-Matthews et al (2001 and Marsh-Matthews and Deaton (2006). Nutrient transfer was quantified by measuring radioactivity present in individual embryos.…”
Section: Radio-tracer Assay Of Matrotrophymentioning
confidence: 99%
See 2 more Smart Citations
“…In short, pregnant females were injected with 8 ll 3 H-leucine (84 Ci/mmole) in the caudal peduncle and 2 h after the injection the females were euthanized using an overdose of MS-222 (Tricaine Methanesulfonate). In the ensuing dissection a sample of the liver was taken to assess uptake of the labeled source by the mother, and individual embryos were carefully dissected from the ovary to remove all maternal tissues, rinsed twice in distilled water and dried for 10 days at 40°C, weighed to the nearest 0.1 mg, and prepared for liquid scintillation assay as described by Marsh-Matthews et al (2001 and Marsh-Matthews and Deaton (2006). Nutrient transfer was quantified by measuring radioactivity present in individual embryos.…”
Section: Radio-tracer Assay Of Matrotrophymentioning
confidence: 99%
“…Nutrient transfer is known to sometimes vary with respect to several factors in poeciliids such as total brood size (Trexler 1997;Marsh-Matthews and Deaton 2006), embryo mass, and developmental stage (Marsh-Matthews et al 2005). These variables were therefore included as covariates in an ANCOVA on the MER-residuals with population as a factor.…”
Section: Radio-tracer Assay Of Matrotrophymentioning
confidence: 99%
See 1 more Smart Citation
“…Fish used in experimental trials generally descend from wild caught individuals, which may slightly reduce the negative consequences of stress due to captivity, such as the agonistic behavior recorded among the wild caught females in this study compared with others (Bisazza et al, 2000). Contrary to some Cyprinodontiformes from other studies elsewhere, whose abdominal distension and/or a visible anal spot are indicators of advanced pregnancy (Bisazza et al, 2000;DeMarais, Oldis, 2005;Marsh-Matthews, Deaton, 2006), the thin females of J. multidentata in this study had embryos that were either ready to birth or were in intermediate stages of development as were depleted of embryos or eggs. This may have hampered the visual monitoring of females next to parturition.…”
Section: Discussionmentioning
confidence: 79%
“…Several studies have suggested that high maternal energy availability during gestation allows females to invest more energy in embryonic development. Such energy allocation is regarded as a selective advantage of matrotrophic reproduction (Trexler and DeAngelis 2003;Marsh-Matthews and Deaton 2006;Ostrovsky et al 2009;Itonaga et al 2012). If this is so, the relationship between food availability and the energetic costs of self-maintenance (i.e., net energy availability) during gestation may play a key role in the evolution of matrotrophic reproduction.…”
Section: Do Gravid Females Become Selfish? Female Allocation Of Energmentioning
confidence: 99%